Peningkatan Pemahaman Guru Madrasah Ibtidaiyah Terhadap Implementasi Kurikulum Merdeka Melalui Best Practice Berbasis Online STAR (Situasi, Tantangan, Aksi, Refleksi Hasil dan Dampak) - Sastra Wijaya; Arifin Maksum; Nina Nurhasanah (Al-Mau'izhoh, 2023)
This study aims to increase the understanding of Madrasah Ibtidaiyah (MI) teachers on implementing the Independent Curriculum through online STAR-based best. The Merdeka curriculum emphasizes developing students' potential and adapting to local contexts, while online STAR-based best practice increases teacher understanding. This research was conducted by involving three teachers. The research method uses phenomenological qualitative research by examining the phenomena experienced by key informants through data collection using observation and semi-structured interviews. Participating subjects in this study were selected using a purposive sampling technique. The study showed increased teacher understanding after using online STAR-based best practices. Hopefully, this research can improve the implementation of the Independent Curriculum at Madrasah Ibtidaiyah.